Trends in counts of Columbiformes at Shakpak Pass, Kazakhstan - BERDIKULOV T. BEKZHAN; FROLOV G. IVAN; GAVRILOV E. ANDREY; TASHIMOV E. AIZHAN; ZARIPOVA KH. SYRYMGUL (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bekzhan BT, Ivan FG, Andrey GE, Aizhan TE, Syrymgul ZKH. 2023. Trends in counts of Columbiformes at Shakpak Pass, Kazakhstan. Biodiversitas 24: 4661-4667. This study aims to determine the trends in counts of Columbiformes (pigeons and doves) at Shakpak Pass in Western Tien Shan (southern Kazakhstan). The analysis is based on long-term ringing data collected from 1966 to 2023, encompassing eight pigeon and dove species. The results reveal notable trends in the counts of Columbiformes over time, which can reflect changes in population sizes. Different species show different numbers in counts among different seasons. The Rock Dove population, predominantly non-migratory, displays no pronounced trend. The Stock Dove population has experienced a decline in recent years, yet it remains consistent throughout the entire research period. Counts of the Woodpigeon demonstrate an increasing trend during autumn migration, whereas the Yellow-eyed Pigeon exhibits a noteworthy decrease in both spring and autumn migrations. The Oriental Turtle Dove appears abundant during both spring and autumn migrations, with its count data exhibiting fluctuations devoid of any significant trend. The Laughing Dove is considered rare at Shakpak Pass, which makes determining a clear trend challenging; however, a negative trend is noted in autumn. Counts of the Turtle Dove have markedly decreased in both spring and autumn migrations, resulting in the species being nearly absent at Shakpak Pass since 2005. Regarding the Collared Dove, a non-migratory species, its abundance at Shakpak Pass is also limited. These findings provide valuable insights into the population trends of Columbiformes in Kazakhstan and highlight the importance of long-term monitoring and conservation efforts for these species.